Taxonomic review of the genus Sicciaemorpha van Eecke (Lepidoptera: Erebidae: Arctiinae), with descriptions of six new species from Malaysia and the Philippines - Volynkin, Anton V.; Černý, Karel (Zootaxa, 2021)
Six new species of the genus Sicciaemorpha van Eecke, 1920 which was previously considered to be monotypic are described: S. yumun sp. n. (Malaysia: northern Borneo Island), S. langgona sp. n. (the Philippines: Mindanao Island), S. nebulibia sp. n. (the Philippines: Luzon Island), S. pleiadina sp. n. (the Philippines: Mindanao Island), S. danepan sp. n. (the Philippines: Mindanao Island), and S. reducta sp. n. (the Philippines: Mindanao Island). Lectotype is designated for the type species of the genus, Sicciaemorpha ivyalba van Eecke, 1920. Adults, male and female genitalia are illustrated.